C-type lectin receptor expression is a hallmark of neutrophils infiltrating the skin in epidermolysis bullosa acquisita - Guerrero-Juarez, Christian F.; Schilf, Paul; Li, Jing; Zappia, Maria Paula; Bao, Lei; Patel, Payal M.; Gieseler-Tillmann, Jenny; Murthy, Sripriya; Cole, Connor; Sverdlov, Maria; Frolov, Maxim V.; Hashimoto, Takashi; et al. (Frontiers in Immunology, 2023)
Inflammatory epidermolysis bullosa acquisita (EBA) is characterized by a neutrophilic response to anti-type VII collagen (COL7) antibodies resulting in the development of inflammatory skin inflammation and blistering. The antibody transfer model of EBA closely mirrors this EBA phenotype. To better understand the changes induced in neutrophils upon recruitment from peripheral blood into lesional skin in EBA, we performed single-cell RNA-sequencing of whole blood and skin dissociate to capture minimally perturbed neutrophils and characterize their transcriptome. Through this approach, we identified clear distinctions between circulating activated neutrophils and intradermal neutrophils. Most strikingly, the gene expression of multiple C-type lectin receptors, which have previously been reported to orchestrate host defense against fungi and select bacteria were markedly dysregulated. After confirming the upregulation of Clec4n, Clec4d, and Clec4e in experimental EBA as well as in lesional skin from patients with inflammatory EBA, we performed functional studies in globally deficient Clec4e -/-and Clec4d -/- mice as well as in neutrophil-specific Clec4n -/-mice. Deficiency in these genes did not reduce disease in the EBA model. Collectively, our results suggest that while the upregulation of Clec4n, Clec4d, and Clec4e is a hallmark of activated dermal neutrophil populations, their individual contribution to the pathogenesis of EBA is dispensable.